Synergy Between Civil Service Investigators at the Natural Resources Conservation Agency and Indonesian National Police Investigators in Law Enforcement Against Pangolin Scale Trafficking - Susi Tutri; Amalia Syauket; Lusia Sulastri (Pelopor Publikasi Akademika, 2026)
West Kalimantan, a region characterized by extensive forest areas and high biodiversity, faces a serious threat from the illegal trade of pangolin (Manis javanica) scales. Law enforcement in the conservation sector involves two investigative institutions, namely Civil Servant Investigators (Penyidik Pegawai Negeri Sipil; PPNS) of the Natural Resources Conservation Agency (Balai Konservasi Sumber Daya Alam; BKSDA) and Indonesian National Police Investigators (Penyidik Kepolisian Negara Republik Indonesia; Polri), which operate within a coordination and supervisory relationship (koordinasi dan pengawasan; Korwas). This study aims to analyze the synergy patterns between the two institutions in investigating criminal acts related to pangolin scale trafficking and to identify obstacles that hinder the effectiveness of such cooperation. The research employed normative legal research (yuridis normatif) with a qualitative approach based on a literature review of primary, secondary, and tertiary legal materials. The collected data were analyzed descriptively and analytically using the legal hermeneutics method. The findings indicate that although the regulatory framework, particularly Law No. 20 of 2025 concerning Criminal Procedure Law and Law No. 32 of 2024 concerning Natural Resources Conservation Agency (Konservasi Sumber Daya Alam dan Ekosistem; KSDAE), clearly regulates the division of functional roles, its implementation in practice remains constrained by sectoral egos, differing interpretations of criminal elements during the P-19 stage, limited forensic resources, and geographical barriers in border areas. This study recommends strengthening the Korwas function, implementing joint investigation training based on asset tracing approaches, enhancing digital forensic infrastructure, and developing permanent operational protocols for institutional synergy to achieve legal certainty and ecological justice.